Research Progress on the Extraction of Natural Tannins - Zhao, Shuyue; Yang, Heying; Li, Ling; Kan, Xurundong (International Journal of Public Health and Medical Research, 2026)
Natural tannins, as polyphenolic compounds widely present in plants, have garnered increasing attention due to their diverse biological activities and industrial applications. This paper systematically examines the current research landscape surrounding natural tannin extraction. Plants such as gallnuts, tea leaves, and tree barks serve as primary sources, with tannins classified into hydrolysable and condensed types based on their chemical structures. Various extraction techniques including solvent extraction, ultrasound-assisted extraction, and enzymatic methods have been developed, each demonstrating distinct advantages in terms of efficiency and environmental impact. Process optimization through parameter adjustment has shown significant improvements in yield and purity. Recent advancements highlight the potential of green extraction technologies that minimize chemical usage while maintaining extraction performance. The extracted tannins exhibit promising applications in leather production, food preservation, and pharmaceutical formulations due to their antioxidant and antimicrobial properties. Future research directions should focus on developing cost-effective large-scale extraction methods and exploring novel applications in emerging fields. Continuous innovation in extraction technologies coupled with sustainable sourcing strategies will be crucial for meeting the growing industrial demand while addressing environmental concerns.